Open Science in Kenya: Where Are We? - Mwangi, Kennedy W.; Mainye, Nyabuti; Ouso, Daniel O.; Esoh, Kevin; Muraya, Angela W.; Mwangi, Charles K.; Naitore, Careen; Karega, Pauline; Kibet-Rono, Gilbert; Musundi, Sebastian; Mutisya, Jennifer; Mwangi, Elizabeth; et al. (Frontiers in Research Metrics and Analytics, 2021)
As research becomes more globalized and its output grows exponentially, especially in data, the need for open scientific research practices is more evident — the future of modern science. This has resulted in a concerted global interest in open science uptake. In most, if not all, the formal training curriculum, universities in Kenya do not equip students with the knowledge and tools to practice open science. Therefore, to work openly and collaboratively, there is a need for awareness and training in the use of open science tools. Moreover, there is scanty research on the state of affairs regarding the practice and/or adoption of open science. Thus, through the OpenScienceKE framework, we developed a model to narrow the gap: sensitize, train, hack, collaborate model. We applied the model in Nairobi to sensitize through seminars, training on the use of tools through workshops, and apply the skills learned in training through hackathons to collaboratively answer the question on the state of open science in Kenya. While the former parts of the model had 20 - 50 participants, the latter part mainly involved participants with a bioinformatics background, leveraging their advanced computational skills. This model resulted in an open resource that researchers can use to publish as open access cost-effectively. Moreover, we observed a growing interest in open science practices in Kenya through literature search and data mining. That lack of awareness and skills may still hinder the adoption and practice of open science. At the time of the analyses, we surprisingly found that out of the 20,069 papers downloaded from BioRXiv, only 18 had Kenyan authors, a majority of which are international (16) collaborations suggesting poor uptake of the use of preprints among Kenyan researchers. The findings in this study highlight the state of open science in Kenya and challenges facing its adoption and practice while bringing forth possible areas for primary consideration in the campaign towards open science. It also proposes a model that may be adopted by researchers, funders, and other proponents of open science to address some of the challenges faced in promoting its adoption in Kenya.